Re-writing the History of Empire in J. M. Coetzee’s Waiting for the Barbarians - Islam LARBAOUI, Ms. Amel BENIA (université mohamed boudiaf .m'sila, 2023)
Abstract This dissertation seeks to shed light on the political nature of the Empire in expanding its influence over the desert, where barbarian tribes and nomads live, by using a contrived truth in order to redeem the idea of the empire in J. M. Coetzee’s Waiting for the Barbarians (1980). Additionally, this research scrutinises the role of torture and violence in constructing the truth of the “Unnamed Empire” in the novel. By the same token, it investigates the impact of torture on a man of conscience. The study also attempts to explore the consequence of oppression that leads to fear of the barbarians and the dehumanisation of society. As the final objective, it inspects the representation of soft power and hard power and how the two main characters, correspond to these types of power respectively. Eventually, it is concluded that these two men are two sides of the same coin, and both are “agents of the empire” whose oppressor consciousness allows them to reconstruct the truth of the empire through both violent power and ideology. To accomplish the research objectives, the dissertation relies on five major theoretical insights: Edward Said’s Culture and Imperialism, Foucault’s theory on Power/Knowledge, Louis Althusser’s ‘Ideology and Ideological State Apparatuses,’ Paulo Freire’s seminal text, Pedagogy of the Oppressed and Tzvetan Todorov’s Fear of Barbarians: Beyond the Clash of Civilizations.
Keywords: Keywords: Truth, Power, History, Violence, Torture, Culture, Imperialism, Empire, Fear of Barbarians.